Fremtidshandel: Fiktionen i den finansielle spekulations tidsalder - Andreasen, Torsten; Eliassen, Knut Ove; Tygstrup, Frederik (K&K - Kultur og Klasse, 2017)
Robert Harris’ novel The Fear Index (2012) takes place over 24 hours on May 6 2010 where the life of eccentric former physicist Alex Hoffmann – now hedge fund owner and developer of trading algorithms – is threatened while the market collapses. It is unclear whether the trader suffers from a schizophrenic psychosis or whether his algorithm VIXAL-4 has actually overpowered him. The fund’s portfolio is “all out of shape” and Hoffmann’s personality “had grown lopsided”, as the algorithmic monster prevails via the complete breakdown of both the market and its maker. Via an analysis of The Fear Index and its references to romantic literature, the article examines the consequences of trade via algorithmic operations beyond human perception and cognition for the relation between cultural imagination and the future.